“‘The Spectre of Marburg’ wanders around the Operative Aesthetics. Luis Juan Guerrero, ‘Evolutive’ Reader of Heidegger” - Belgrano, Mateo (2023)
“‘The Spectre of Marburg’ wanders around the Operative Aesthetics. Luis Juan Guerrero, ‘Evolutive’ Reader of Heidegger”. This paper aims to analyse the reading of Martin Heidegger’s thought offered by Luis Juan Guerrero in his Operative Aesthetics. I claim that “The Origin of the Work of Art” plays a central role in the work of the Argentinian philosopher. However, this does not mean that Guerrero is not an original author or that he is a mere commentator of the German philosopher. On the contrary: the Argentinian philosopher offers a productive reading of Heidegger which allows him to build his own and authentic philosophy. By focusing on Heidegger’s essay on art and on the first volume of the Operative Aesthetics, this paper analyses three essential issues: the concept of tool, the world-earth relationship, and the bond between history and truth.